JADIDISM, AUTONOMY, INDEPENDENCE (Scientific journal of the Fergana State University, 2024)
The article describes the social and political factors that led to the emergence of Jadidism. The role and importance of jadids in the life of Turkestan in the second half of the 19th century - the beginning of the 20th century is analyzed. The establishment of the Turkestan Autonomous Region, its subsequent bloody dissolution by the colonialists, and the reflection of these bloodsheds in modern literature are covered. In the analysis of the topic, the works of Mustafa Chokai oglu, Mahmudhoja Behbudi, Hamza Hakimzada Niyazi, Abdulhamid Cholpan were referred to.